Encapsulação de óleo de café verde rico em cafestol e caveol por coacervação complexa e aplicação em suco de tamarindo (Tamarindus indica L.) - Oliveira, Williara Queiroz de (2019)
Green coffee oil (GCO), rich in cafestol and caveol, has functional effects related to the antiproliferative action of cancer cells, anti-inflammatory capacity and antidiabetics. However, challenges need to be overcome for direct application of this oil in the food matrix; matrix due to the instability of its bioactive compounds, specially diterpenes. Complex coacervation is a reproducible and non-costly encapsulation technology, which proposes to overcome the technological challenges of the incorporation of oils, allowing its application with greater stability. The objective of this work was to design and characterize GCO microcapsules, rich in cafestol and caveol, using them as an ingredient in tamarind juice, investigate the effects on the physical-chemical, rheological and sensorial quality of the beverage, in addition to quantifying the gastrointestinal release in vitro and checking the resistance of best microcapsule selected to stress (agitation, T, pH). Among six formulations, the T6 microcapsules, gelatin and cashew gum walls (GE / GC), showed a better biopolymer combination for application in juice, better dispersive capacity and resisting to temperature of 100 ° C / 30sec, higher than those used in pasteurization. When the amount of GCO was varied, T625 (sectioned as the best particle for application in juice) exhibited microcapsules (14.56 ± 6.36 μm) capable of better preservation of the encapsulated oil, with good encapsulation efficiency (85.57 ± 1.41%) and twelve-fold oxidation protection higher than nonencapsulated GCO. There was no detection of cafestol released by the microcapsules when they were submitted to different pH values (2.5-6.5) or when they were applied in juice during storage (30 days). With good sensory quality, the juice with T625 presented pH between 3.20 ± 0.01 to 3.67 ± 0.01, total soluble solids (TSS) of 7.13 ± 0.15 to 8.07 ± 0.21 ° Brix and total titratable acidity (TTA) of 1.08 ± 0.07 to 0.67 ± 0.20%. The viscosity of the beverage was 11.7 ± 8.4 at 15.2 ± 2.6 (mPa.s), without significant differences (p <0.05) among control (Tj1), juice and free oil (Tj2) and juice with GCO microcapsules (Tj3), without compromising the quality of the final product. This study showed that encapsulation of green coffee oil by complex coacervation was possible, in addition to promoting the production of coffee-rich and caveol rich juice, without altering its physical-chemical, rheological and sensorial properties when compared to conventional tamarind juice; thereby providing a broad perspective on the application of GCO microcapsules for incorporation into food products of hydrophilic matrix.